A new liquid-phase method and its comparison to two solid-phase microbial respiration activity methods to assess organic waste stability. (1st February 2020) - Evangelou, Alexandros; Komilis, Dimitrios
Highlights: A liquid phase stability test (MANLIQ) was compared to 2 solid-phase stability tests. The respiration indices' order was: Dynamic > MANLIQ ≥ Static. The strongest correlation was between the liquid and the static solid-phase indices. The ratio of the liquid indices to the static solid-phase indices was 1.6–2.7. The solid phase tests should be preferred over the liquid test to assess stability. Abstract: Goal of the work was to compare the respiration activities, as measured via oxygen consumption with three different organic waste stability methods so that to propose the optimal one. The novelty of the work is that there exists no comparison of solid-phase with liquid-phase stability assessment techniques in the literature. The respiration activities were assessed using two solid-phase methods and a manometric liquid-phase method (MANLIQ) performed on twenty-seven organic substrates. The methods rely on measuring oxygen consumption (uptake) via pressure drops (liquid-phase test, static solid-phase test) or via direct O2 measurements on the gaseous phases at the inlet and outlet of the respirometer (solid-phase dynamic test). A positive statistically significant correlation was calculated between the MANLIQ and the static solid-phase indices. The maximum rate MANLIQ index for the raw substrates was 2900 mg O2 kg −1 VS h −1, while most of the processed substrates had cumulative MANLIQ indices below 160 g O2 kg −1 VS. The ratio of the liquid indices to the static solid-phase indices ranged from 1.6 to 2.7 and the ratio of the liquid indices to the dynamic solid-phase indices ranged from 0.2 to 0.4. The MANLIQ method failed to result in a good correlation of the processing time with the respiration indices. On the other hand, a correlation was more visible in the two solid-phase tests, despite the large variability of the types and sources of the substrates. Therefore, the solid-phase methods should be preferred over the liquid-phase method to assess stability for various organic substrates.